ANALISIS FASILITAS PEJALAN KAKI PADA RUAS JALAN GAJAH MADA, DENPASAR, BALI - Preantjaya Winaya, Putu (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 1 Januari 2010, 2012)
Transportation problems at Jalan Gajah Mada Denpasar are due to the increasing in population and number of vehicles, unncreasing length of the road, and no development for urban public transport. It is expected that city arrangement can developed new scenery in which the perpetrators of activities can reduce the use of of private vehicle and to choose public transport where the main target of public transport users are pedestrians. This requires the provisions of pedestrian facilities to be comfortable and safe that can support the activities during the postand pre-trip using public transportation. A study conducted in Jalan Gajah Mada Denpasar aims to analyze the characteristics and service facilities at the pedestrian in Gajah Mada streets of Denpasar. The research method used is by observation and data collection directly in the field. The analysis result shows that the flow range of pedestrians on the Old North Side Trotoar is from 0.024 to 0.293 people/m/min, the Old South Trotoar is 0.081 to 1.305, the New North Trotoar is 0.2 to 1.12 and the New South Trotoar is 0.062 to 0.803 people/m/min. The average speed of pedestrian space for the Old North Trotoar, the Old South Trotoar, The New North Trotoar and the New South Trotoar ranges from 48 to 56 m/min, 51 to 80, 47 to 81 and from 48 to 87 m/min, respectively. Density of pedestrians on the Old North Trotoar the Old South Trotoar, The New North Trotoar and, the New South Trotoar ranges between 0 and 0.0056 person/m², 0.0009 and 0.017, 0.003 and 0.018, and 0.0009 and 0.009 people/m² respectively. Pedestrian space in the Old North Trotoar ranges from 178.42391 m²/person up to ~ m²/person, the Old South Trotoar is 57.64018 to 1011.183, the New North Trotoar is 53.92405 to 329.8371, and the New South Trotoar is between 107.0526 and 1092.299 m²/person. It is found that the level of service based on pedestrian space facilities at the largest 15-minute flow is the “A” category service level. To improve safetiness and comfortiness of pedestrians, it is advisable to complete the pedestrian facility and to enforce the Mass Public Transportation in order to reduce the vehicle flow.
Keywords: Characteristics and Pedestrian Facility Services